2022
DOI: 10.3389/fanim.2022.872776
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Response Investigation of a Micronized Porous Ceramic Particle to Improve the Health and Performance of Post-weaned Pigs Infected With Salmonella enterica Serotype Typhimurium

Abstract: The objective was to investigate the effects of supplementing increasing concentrations of PowerGuard (PG), a micronized ceramic particle, to weaned pigs on health and performance following a Salmonella enterica serotype Typhimurium infection. Forty barrows were transported to the USDA facility in Liberty, TX, USA. Pigs were randomly assigned to one of five treatments (n = 8): (1) uninfected control (CON), no Salmonella typhimurium (ST) and no PG treatment; (2) infected control (ST), infected with ST but no PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, such a range of doses results in different outcomes. Some authors reported models with mild infectious outcomes [ 14 , 15 , 16 ]; while other studies showed clinical responses [ 17 , 18 ], and even responses that overwhelmed treatment capacity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, such a range of doses results in different outcomes. Some authors reported models with mild infectious outcomes [ 14 , 15 , 16 ]; while other studies showed clinical responses [ 17 , 18 ], and even responses that overwhelmed treatment capacity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%